AB0696 Phenotype Difference in Familial Ankylosing Spondylitis (AS) Compared to Sporadic as in Korea. (10th June 2014) - Kim, H.W.; Choe, H.R.; Lee, S.B.; Chang, W.I.; Chae, H.J.; Moon, J.Y.; Kang, J.; Lee, S.; Song, Y.W.; Lee, E.Y.
Abstract : Background: Clustered occurrences of ankylosing spondylitis (AS) in the family have been noticed. Few phenotype studies on familial AS suggest the distinct features of the disease compared to sporadic disease. Objectives: The aim of this study is to investigate clinical characteristics and incidence of familial form of AS compared to sporadic AS. Methods: We evaluated patients with AS confirmed by the modified New York criteria for familial history of AS (one or more first to third degrees relatives). The clinical characteristics and the recurrence risks (number of AS patients/number of familial members) of the familial AS compared to sporadic AS were investigated. Results: Out of a total of 204 AS patients (165 males, 39 females, mean age 37.0±13.1 years), 38 patients (18.6%) reported that they had a familial history of AS. The recurrence risks in the familial AS patients for first, second and third degree family members were 14.5%, 5.2%, and 4.4% respectively. ESR (22.6±22.2 vs. 35.4±34.4, p=0.029) and CRP (1.24±1.7 vs. 2.43±3.3, p=0.003) at diagnosis, body mass index (21.9±2.7 vs. 23.7±3.3, p=0.002) and frequency of oligoarthritis (13.2% vs. 33.7%, p=0.021) were significantly lower in the familial form. The presence of HLA-B27 (97.4% vs. 83.1%, p=0.044) was significantly higher in familial AS. Conclusions: We report that Korean AS patients with a familial history had a higher presence of HLA-B27 than sporadic AS. The recurrence risk in the familial AS was highest in first degree relatives, indicating higher susceptibility to the disease. Distinct phenotypes of familial AS were lower frequency of oligoarthritis, lower ESR and CRP at diagnosis and lower body mass index. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3469